Legal basis liability for national and international legislation - Козачок, Ірина Ярославівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
This article attempts to analyze the content of the international conventions and protocols related to aviation safety, which Ukraine (USSR) and the related issues of national legislation in the field of safety